VD_FINDINFO Décision / 2021 / 297 vom 31. März 2021 - VD Tribunal cantonal (2021)
NON-LIEU, HONNEUR, INFRACTIONS CONTRE L'HONNEUR, ADMISSION DE LA DEMANDE | 173 ch. 1 CP, 173 ch. 2 CP, 173 ch. 3 CP, 174 ch. 1 CP, 310 CPP (CH)